1975
DOI: 10.1002/aic.690210515
|View full text |Cite
|
Sign up to set email alerts
|

Flow phenomena in stirred tanks. Part I. The impeller stream

Abstract: Flow parameters were measured in a baffled, turbulent, stirred tank agitated by a six-blade, disk style turbine. The working fluid was air. Mean and fluctuating velocities were measured between the blades of the impeller with a probe mounted on the spinning impeller. Mean velocities, turbulent velocities, one-dimensional energy spectra, and Eulerian autocorrelation functions were measured in the impeller stream by using the shielded hot-wire anemometer of Gunkel et al. (1971) which permits the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…He concluded that around 20% of the total kinetic energy is dissipated in the impeller region, 50% in the impeller stream and 30% in the bulk. Although Gunkel and Weber (1975) used a similar approach to Cutter (1966), they found that most of energy was dissipated in the bulk of the tank and not in the impeller region or impeller discharge. The main reason for this disagreement may be the difference in the D/T ratio.…”
Section: Kinetic Energy Balancementioning
confidence: 95%
See 1 more Smart Citation
“…He concluded that around 20% of the total kinetic energy is dissipated in the impeller region, 50% in the impeller stream and 30% in the bulk. Although Gunkel and Weber (1975) used a similar approach to Cutter (1966), they found that most of energy was dissipated in the bulk of the tank and not in the impeller region or impeller discharge. The main reason for this disagreement may be the difference in the D/T ratio.…”
Section: Kinetic Energy Balancementioning
confidence: 95%
“…The main reason for this disagreement may be the difference in the D/T ratio. Cutter (1966) used an impeller of D = 0.3 T whereas Gunkel and Weber (1975) used an impeller diameter of 0.5 T. Furthermore, from 2-D PIV measurements of the flow field in RDT stirred flows (Khan, 2005) it has been found that the axial velocity component is not small enough to be neglected. The flows generated by the PBT have strong axial components and so Cutter's Eq.…”
Section: Kinetic Energy Balancementioning
confidence: 98%
“…3. [14] and the pitched blade turbines [13]. This difference is due to the elimination of periodic oscillations from the autocorrelation coefficient.…”
Section: The Scales Of Turbulencementioning
confidence: 94%
“…The calculation of the turbulence characteristics from the energy spectrum requires a large definition of the one-dimensional energy spectrum. Gunkel and Weber [13] estimate the maximum dissipation of the kinetic energy in the range of 10 Hz±1 kHz, a sampling frequency equal to 2 kHz appears sufficient to calculate the turbulent characteristics. The problem is that this value of the sampling frequency cannot be obtained in the whole tank.…”
Section: Influence Of the Sampling Frequencymentioning
confidence: 99%
See 1 more Smart Citation